Co-evaporated p-i-n perovskite solar cells with sputtered NiOₓ hole transport layer - Erdenebileg, Enkhtur (2023)
Metal oxides have long been used as charge transport layers in thin film solar cells due to their suitable energy band levels, high charge carrier mobilities, and excellent long-term stability. One example is non-stoichiometric nickel oxide (NiOx), a hole transport material which can be deposited in a conformal, scalable, and solvent-free manner via sputtering. However, sputtered NiOx has only ever been combined with spin-coated perovskite films in perovskite solar cells (PSCs). Here we report the fabrication of the first co-evaporated PSCs with sputtered NiOx as the hole transport layer. We reveal how the amount of argon gas used during sputtering affects important physical properties such as hole conductivity, visible light transmittance, and suitability of the NiOx surface for perovskite nucleation and growth. Optimized sputtering conditions led to CH3NH3PbI3 (MAPbI3) PSCs with an 18.6% power conversion efficiency (PCE), which was further increased to 19.5% by adding a spiro-TTB interlayer between NiOx and MAPbI3. We also show that removing the NiOx annealing step only reduced the device PCE by 1%, paving the way toward low-temperature deposition of metal oxide transport layers. This work exhibits the versatility of NiOx sputtering and perovskite evaporation as a powerful combination for solvent-free and low-temperature fabrication of highly efficient PSCs.